Hubungan Aktivitas Fisik Dengan Kejadian Konstipasi Pada Lansia Di Kelurahan Cipadu Jaya Kota Tangerang - Suroso; Tantri Wenny Sitanggang; Susilawati Susilawati; Riska Andini (Jurnal Kesehatan STIKes IMC Bintaro, 2023)
ABSTRACT Background: Constipation is a common health problem experienced by humans and affects the well-being and quality of life of patients in clinical practice. This is indicated by one fifth of the population experiencing chronic constipation Research Objectives: To determine the relationship between physical activity and constipation in the elderly in the Cipadu Jaya environment, Tangerang City Methods: This research is a descriptive analytic study with a cross sectional study design. The sample in this study was 32 elderly people living in the Cipadu Jaya Ward, Tangerang City, according to the inclusion criteria. Research Results: The results of statistical tests show that there is a relationship between physical activity and the incidence of respondents' constipation with a p value of less than 0.05, which is 0.023 Suggestion: It is necessary to increase vigilance in elderly patients who suffer from constipation, so that the incidence of recurrent constipation can be avoided.